THE INFLUENCE OF ORGANIZATIONAL CLIMATE, AND ACHIEVEMENT MOTIVATION OF LABOR ACHIEVEMENT IN FACULTY OF EDUCATION SCIENCE (FIP) PADANG STATE UNIVERSITY (UNP) - Anisa Anisa (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to reveal the influence of organizational climate and achievement motivation on employee performance lecturer at the Faculty of Education, State University of Padang. The population was all lecturers at Faculty of Education UNP consist of 174 lecturer and sample were 55 lecturers. The research data was collected using a questionnaire Likert scale model. The data were analyzed by using descriptive and inferential statistics. The results showed that: 1) Organizational climate positively affect work performance; 2) achievement motivation has positive and significant impact on work performance lecturers; 3) Organizational climate and achievement motivation has positive and significant impact on work performance lecturers of Faculty of Education UNP 31.6%.